Double stratification effects on unsteady electrical MHD mixed convection flow of nanofluid with viscous dissipation and Joule heating - Daniel, Yahaya Shagaiya; Aziz, Zainal Abdul; Ismail, Zuhaila; Salah, Faisal (Journal of applied research and technology, 2017)
The problem of unsteady mixed convection electrical magnetohydrodynamic (MHD) flow and heat transfer induced due to nanofluid over a permeable stretching sheet using Buongiorno model is investigated. The transverse electric and magnetic fields are considered in the flow field, while in the heat convection is associated with the thermal radiation, heat generation/absorption, viscous and Ohmic dissipations, and chemical reaction is incorporated in the mass diffusion. A similarity transformation is used to reduce the boundary layer governing equations which are partial differential equations to nonlinear differential equations and then solved numerically using implicit finite difference scheme. The nanofluid velocity and temperature are sensitive to an increase in the electric field, which resolved the problem of sticky effects due to the magnetic field. Destructive chemical reaction increases the level nanoparticles concentration while reversed behave happened in the case of the generative chemical reaction. Heat source boosts the fluid temperature while as opposite occurred with the heat sink. Thermal and concentration stratifications decreased the fluid temperature and the nanoparticles concentration profiles. Buoyancy ratio parameter reduced the Nusselt and Sherwood numbers whereas mixed convection parameter increases for higher values. A comparison with the previous study available in literature has been done and found an excellent agreement with the published data.